Designing UI/UX for Academic Module of Education Management System Using Design Thinking - Kristiawan, Yohanes Nico; Al Anshary, Faishal Mufied; Lathifah, Syfa Nur (Jurnal Teknologi Informasi dan Pendidikan, 2025)
Learning is the process of altering behavior through the acquisition of knowledge, useful skills, and moral precepts from a variety of sources. The role of media in education is becoming more and more important in the current digital era to improve human resources. By improving resource management, openness, and information exchange, education management systems raise academic standards. The COVID-19 pandemic has sped up digital learning, but issues with accessibility and flexibility still exist and require creative solutions. The digitalization of education is getting closer to reality thanks to growing internet usage, improved infrastructure, and greater technology literacy. The Education Management System (EMS) website at SMPN 1 Magetan was created using a Design Thinking methodology, which is examined in this paper. The goal of the academic module design is to improve user experience and management effectiveness. Key system features were defined by analyzing the user needs that were discovered through interviews. Low-fidelity wireframes were the first step in the design process, which continued to high-resolution prototypes. The prototype, when tested using the Maze tool, received a pleasant and user-friendly experience, with an average System Usability Score (SUS) of B and a Single Ease Question (SEQ) score of 5.5 to 6.0 out of 7 from all role like Student, Teacher, Parent, and Administrative Staff.